Presence of low virulence chytrid fungi could protect European amphibians from more deadly strains - Mark S. Greener (Nature Portfolio, 2020)
The pathogen Batrachochytrium dendrobatidis (BD) associated with widespread amphibian declines is present in Europe but has not consistently caused disease-induced declines in that region. Here, the authors suggest that an endemic strain of BD with low virulence may protect the hosts upon co-infection with more virulent strains.